Total laparoscopic hysterectomy: why surgeon teachers must learn and train residents - Valecha, Shalini Mahana; ., Pandeeswari; Bashani, Dolly; Syed, Saman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The purpose of the present study is to demonstrate the feasibility of laparoscopic surgery for hysterectomy and elaborate our experience. Methods: Between September 2017 and April 2018, 15 patients who were counselled for and opted for total laparoscopic hysterectomy our hospital enrolled in this study. Surgeons used a four-port system with, one 10mm and three 5-mm trocars. All surgical procedures were performed with 30°, 10-mm laparoscope and conventional laparoscopic instruments including monopolar and bipolar cautery system and the LigaSure system. Patient’s history, clinical findings and surgical outcomes were prospectively tabulated, evaluated and analyzed. Results: Out of 15 patients under the study with age range of 40-55years, only 2 patients had hypertension and diabetes mellitus and 2 had anaemia. All 15 patients underwent conventional laparoscopic surgery. Operative time was in a range of 6O–240 min. There were no intra operative complications in 6 patients (40%) and no post op complications in 11 women (73%). Conclusions: The results from our 15 women show that, in experienced hands, laparoscopic hysterectomy is not associated with any increase in major complication rates.